(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Today, the United States is one of the leading countries that actively uses digital diplomacy in its interactions with foreign societies and governments. With the development of modern information and communication technologies, the role of digital diplomacy is becoming increasingly important. This form of diplomacy not only facilitates effective communication between countries, but also allows for influencing public opinion and relations with governments.